Correlating research impact of library and information science journals using citation counts and altmetrics attention. Issue 3 (19th August 2019) - Ezema, Ifeanyi Jonas; Ugwu, Cyprian I.
Abstract : Purpose: Since the development of web 2.0, there has been a paradigm shift in methods of knowledge sharing. This has equally impacted on techniques of research evaluation. Many scholars have argued that the social utilization of research is hardly reflected in the traditional methods of research evaluation. The purpose of this paper is to determine the research impact of Library and Information Science (LIS) journals using Web of Science (WoS), Scopus and Google Scholar (GS) and then examine whether there is a correlation between their citations and altmetric attentions. Design/methodology/approach: This paper is an attempt to contribute to this discussion with focus on the field of LIS. This paper adopted descriptive informatics to analyze LIS journals. The paper extracted citation data from WoS, Scopus and GS, and altmetric attentions from 85 LIS journals indexed by WoS. Further, 18 journals with high altmetric attention were identified, while 9 of these maintained consistent presence in the three databases used. Findings: Findings show that of these databases, citation data from GS was found to have a high correlation with altmetric attention, while the other two databases maintained moderate correlations with altmetric attention. The paper also found a positive but non-significant correlation between citation scores and altmetric attention in the nine journals that maintained consistent presence in the three databases. Practical implications: The findings of this paper will be useful to librarians in selection of relevant journals for their libraries and also will assist authors in the choice of publication outlets for their papers particularly when considering journals that have visibility and research impact. Originality/value: The originality of the paper lies on empirical evidences from the citation and altmetric data extracted from the databases used for the paper.